Predicting Economic Activity Using the Slope of Yield Curve : A Study of Indian Economy - Rangotra, Rahul (Indian Journal of Finance, 2020)
This study examined the impact of slope of yield curve on the output in the Indian economy. Two definitions of the slope are used in the paper. Slope1 (difference between 10-year and 3-months government securities yield) and Slope2 (difference between 10-year and 1-year government securities yield). It was found that Slope1 and Slope2 had a significant impact on percentage change in index of industrial production (IIP), but the Slope2 was observed to a better predictor than Slope1 (at least for the Indian economy) as beta-coefficient and t - stat were found to be greater in Slope2 than in Slope1. Also, Slope1 had maximum impact on IIP after 7 months (lags) and Slope2 had maximum impact after 8 months (lags). The study found no significant relation between slope and the percentage change in gross domestic product (GDP) and broad market index (Sensex). The study can be used by researchers and forecasters to predict the recession in the Indian economy.